SISTEM SPASIAL PENGELOLAAN SAMPAH PERMUKIMAN BERBASIS MASYARAKAT (BANK SAMPAH) DI KOTA YOGYAKARTA - Sarasati, Carina; Pandelaki, Edward Endrianto; Sari, Suzanna Ratih (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2018)
Abstract:. The city of Yogyakarta has a waste problem where there is an imbalance between the amount of waste generated and waste management space. Therefore, community-based waste management was appear in the form of â€Garbage Bankâ€ which expected to manage the inorganic waste at RW level. The existence of the â€œGarbage Bankâ€ is supported by the Mayor of Yogyakarta program and also some policies of the Central and Regional Governments. However, in reality there is no spatial system of waste management of settlements which clear and integrated through